IMPLEMENTING DISASTER SAFE EDUCATION THROUGH BEST DISASTER MITIGATION - Elda Farhana; Musrikah Musrikah (Muallimun : Jurnal Kajian Pendidikan dan Keguruan, 2026)
Indonesia is highly vulnerable to natural disasters due to its location along the Pacific Ring of Fire. This condition necessitates integrating disaster risk reduction into educational systems, particularly in early childhood education. However, empirical studies on the implementation of disaster-safe education at this level remain limited. This study aims to analyze the implementation of disaster-safe education and identify its strengths and challenges at Aisyiyah Bustanul Athfal (ABA) Penjor Early Childhood Education Center in Tulungagung, East Java, Indonesia. This study employed a qualitative exploratory approach, collecting data through observations, interviews, and documentation with teachers and members of the Disaster-Safe Education Unit. The researchers analyzed the data using an interactive model involving data reduction, data display, and conclusion drawing, supported by triangulation to ensure validity. The findings indicate that educators implement disaster-safe education through experiential learning activities, including self-rescue simulations, hazard identification, first-aid training, and traditional early warning systems rooted in local wisdom. These practices significantly enhance children's awareness, preparedness, and responsiveness to disaster risks. Nevertheless, challenges such as limited infrastructure and resources persist. This study contributes to the growing body of knowledge on disaster education by providing empirical evidence of effective disaster mitigation practices in early childhood settings. The findings highlight the importance of integrating disaster-safe education into early childhood curricula to foster resilient and disaster-prepared generations.